A simple and rapid resonance Rayleigh scattering method for detection of indigo carmine in soft drink. (20th January 2016) - Li, Qin; Yang, Jidong; Tan, Xuanping; Zhang, Zhan; Hu, Xiaomei; Yang, Menghuan
Abstract: A novel method that uses acridine orange (AO) to detect indigo carmine (IC) in soft drinks was developed. The method is highly sensitive and is based on a resonance Rayleigh scattering (RRS) technique. In Britton–Robinson (BR) buffer solution, pH 4.3, the weak RRS intensity of AO was greatly enhanced by the addition of IC, with the maximum peak located at 332 nm. Under optimum conditions, it was found that the enhanced RRS intensity was proportional to the concentration of IC over a range of 2–32 × 10 −6 mol/L. A low detection limit of 2.4 × 10 −8 mol/L was achieved. The sensitivity and selectivity of the method are high enough to permit the determination of trace amounts of IC without any significant interference from high levels of other components such as common anions and other amino acids. Finally, the concentration of IC in three different soft drinks was determined with satisfactory results. Copyright © 2016 John Wiley & Sons, Ltd.